Misinterpretation on rumors towards racial conflict: a review on the impact of rumors spread during the riot of May 13, 1969 - Al-Amril Othman,; Mohd. Nor Shahizan Ali, (Penerbit Universiti Kebangsaan Malaysia, 2018)
A rumor is a short-lived, unverified report, usually anonymous in its origin. Rumor exists, especially in a turbulent society. In fact, a plural society that comes from various background exhibits greater potential of its dissemination due to the diversity of aspirations and interpretations in obtaining information based from opinion differences. Malaysia had experienced the problem during the riots in Kuala Lumpur on May 13, 1969. The spread of rumors does not only affect the life victims and the destruction of the property, but also determines the path and direction of the nation’s politics. This change is in line with the prohibition of debate on sensitive matters which are enshrined in the constitution. The objective of this article is to assess the relationship between rumors and conflicts in a society. The initial discussion focuses on factors that determine the rate of spread in the society. It focuses on the authorities measures, inclusive of safety, administrative and legislative measures to control its dissemination. Finally, it focuses on the short, medium, and long-term implications arising from its dissemination. It can be concluded that the May 13 incident is an effective mechanism in controlling the conflict in the country. This does not mean that the spread of rumors specifically on negative matters will be discontinued. It relies heavily on the government’s sensitivity towards the current situation, therefore, necessary actions should be taken to address the dissemination in order to avoid similar events to recur.